1980
DOI: 10.1530/acta.0.0930365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ACTH on the proliferative and secretory activities of the adrenal glomerulosa

Abstract: The mitotic, trophic and secretory responses of the adrenal cortex to various preparations and doses of ACTH were investigated in the rat. 1-24-ACTH depot (Synacthen) elicited the highest mitotic and trophic stimulation. The mitotic stimulation occurred exclusively in the glomerulosa, the trophic stimulation occurred mainly in the fasciculata-reticularis and the functional stimulation was found in both, as indicated by the plasma aldosterone and corticosterone levels. The functional changes occurred first, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…It is well documented that in vivo ACTH administration or its hypersecretion causes primarily adrenocortical cellular hypertrophy, which is subsequently followed by hyperplasia (16,31,(49)(50)(51)(52)(53)(54)(55)(56)(57). On the contrary, the direct in vitro effect of ACTH involves inhibition of adrenocortical cell proliferation and stimulation of the cell specialized functions, that is corticosterone secretion (28,34,(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that in vivo ACTH administration or its hypersecretion causes primarily adrenocortical cellular hypertrophy, which is subsequently followed by hyperplasia (16,31,(49)(50)(51)(52)(53)(54)(55)(56)(57). On the contrary, the direct in vitro effect of ACTH involves inhibition of adrenocortical cell proliferation and stimulation of the cell specialized functions, that is corticosterone secretion (28,34,(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…The stimulating effect of NMU8 on ZG cells in ACTH-treated rats was similar to that evoked by ACTH alone. ZG of adrenal cortex is a proliferative region provided with stem cells, and newly formed cells from that region differentiate and migrate centripetally through the ZF into the zona reticularis (ZR), where they undergo apoptosis (31,(51)(52)(53)56,(68)(69)(70)(71)(72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of this agent on aldosterone production by adrenal zona glomerulosa is not known. We have reported that in vivo administration of ACTH increased mitotic activity in rat adrenal zona glomerulosa [9,10]. Rats treated with ACTH produced an increase in plasma corticosterone and aldosterone levels when compared to controls injected with saline [lo].…”
Section: Introductionmentioning
confidence: 99%
“…Rats treated with ACTH produced an increase in plasma corticosterone and aldosterone levels when compared to controls injected with saline [lo]. However, when colchicine was administered to controls and to groups of rats treated with ACTH on purpose to block mitosis, no differences could be observed in plasma aldosterone and corticosterone levels between the groups studied [9]. To clarify discrepancies between results obtained when colchicine was included or omitted in our experiments, we have examined here the effect of the in vivo administration of colchicine, or ACTH, or colchicine with ACTH on rat plasma aldosterone and corticosterone levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation